2008
DOI: 10.1097/bcr.0b013e31818481bc
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Clinical Outcomes Associated With Elevated Blood Alcohol Levels at the Time of Burn Injury

Abstract: Elevated blood alcohol content (BAC) on admission is associated with poorer outcomes, larger burns and more inhalation injury. This study’s purpose was to examine the effects of alcohol through a matched case-controlled study, measuring early and extended markers of clinical outcomes. The hypothesis was that patients with an elevated admission BAC would require more resuscitation and have a longer hospital stay. Admissions 16 to 75 years of age with 15 to 75% TBSA and admission BACs were identified. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 32 publications
3
76
0
Order By: Relevance
“…Approximately one million burn injuries are reported every year within the United States, and nearly half of them occur in individuals who are under the influence of alcohol/ethanol (EtOH) (1)(2)(3). Studies have shown that patients who are intoxicated at the time of injury are more susceptible to infection and have a higher incidence of mortality compared with burn patients who have not consumed EtOH at the time of injury (2,4,5). Similarly, findings from experimental studies have also shown that EtOH intoxication before burn injury exacerbates the suppression of immunity, impairs intestinal barrier function, and increases bacterial translocation relative to either EtOH intoxication or burn injury alone (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 69%
“…Approximately one million burn injuries are reported every year within the United States, and nearly half of them occur in individuals who are under the influence of alcohol/ethanol (EtOH) (1)(2)(3). Studies have shown that patients who are intoxicated at the time of injury are more susceptible to infection and have a higher incidence of mortality compared with burn patients who have not consumed EtOH at the time of injury (2,4,5). Similarly, findings from experimental studies have also shown that EtOH intoxication before burn injury exacerbates the suppression of immunity, impairs intestinal barrier function, and increases bacterial translocation relative to either EtOH intoxication or burn injury alone (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 69%
“…Nearly one million burn injuries are reported in the United States every year, and 50% of these injuries occur in individuals under the influence of alcohol/ethanol (EtOH) (4)(5)(6)(7)(8). Studies indicate that intoxicated patients have higher rates of septic complications, longer hospital stays and increased mortality compared with patients who have a similar extent of burn injury but did not consume EtOH before injury (7)(8)(9)(10)(11). There is evidence that EtOH intoxication combined with burn injury abrogates the host immune system.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of consuming enough alcohol to bring the blood alcohol concentration to Ն0.08%, known as binge drinking, is an increasingly prevalent form of intoxication (39) and the characteristic consumption pattern among patients presenting with traumatic injury, including burns (46). Approximately half of adult burn patients are intoxicated at the time of admission, and these patients have worse clinical outcomes than individuals who sustain similar injuries without alcohol exposure (23,29,48). Specifically, they are twice as likely to acquire an infection, undergo 60% more surgical procedures, require more days on mechanical ventilation, and stay longer in the intensive care unit (6,48).…”
mentioning
confidence: 99%